IMPLEMENTASI KEBIJAKAN PERDA NO 5 TAHUN 2011 TENTANG RETRIBUSI PENGUJIAN KENDARAAN BERMOTOR (STUDI DI KANTOR DINAS PERHUBUNGAN KOTA PALANGKA RAYA) - Susilo Mangun Budi Raharjo (Journal Ilmu Sosial, Politik, dan Ilmu Pemerintahan, 2019)
This study focused on the implementation of the Regional Regulation of PalangkRaya City Number 5 of 2011 concerning Motor Vehicle Testing Retribution. Thpurpose of this study was to find out how the implementation of the RegionalRegulation of Palangka Raya City Number 5 of 2011 concerning Motor VehicleTesting Retribution and supporting factors as well as the inhibiting factors ofPerda Policy Implementation Number 5 of 2011 concerning Study of VehicleMotor Tests at the Office of Transportation of Palangka Raya. In a study thatraised the title of implementation of the Regional Regulation of Palangka RayCity Number 5 of 2011 concerning Motor Vehicle Testing Retribution, thresearcher used the Merilee S. Grindle theory which had 9 variables viewed fromthe contents of the policy and policy environment. This research was conductedusing a qualitative-descriptive approach. The data obtained in this study werecollected through interviews, observation, library studies, and communication.Data that has been successfully collected in this study is processed and analyzedusing qualitative analysis procedures with interactive data analysis techniquesnamely data reduction, data presentation, and conclusion / verification. The resultof this study are the implementation of the Regional Regulation of Palangka RayCity Number 5 of 2011 concerning Motor Vehicle Testing Retribution has beengoing well, especially on the indicators of decision making and the power ofinterests and strategies of the actors involved. However, there are inhibitingfactors, namely there are still people, especially public transport drivers, who donot know about City Regulation No. 5 of 2015 concerning Vehicle TestingRetribution. And testing units and testing facilities that are not good yet includtesting unit standards and from the dissemination of the relevant RegionaRegulations have not touched all elements of society especially motorists, namelyPublic Transportation, this is related to the absence of budget and low awareness of vehicle owners, especially fleets public transportation on the importance oftesting motorized vehicles.